Analisis Kebutuhan Kompetensi Pembelajaran Kewirausahaan Progran Studi S3 Pendidikan Vokasi Keteknikan Pascasarjana UNM - Hasanah Hasanah; Muhammad Nasir Malik (Seminar Nasional LP2M UNM, 2021)
Abstract. 21st Century Education is education that integrates knowledge, skills, and attitudes, as well as mastery of Information and Communication Technology (ICT). The aims of this research are: (1) to analyze 21st century competencies, based on the needs of the global community; (2) identify the need for S3-PVKT PPs UNM Entrepreneurship learning competencies; (3) identify entrepreneurial competencies that support S3-PVKT Entrepreneurship learning competencies. This type of research is descriptive research with a qualitative approach. Based on this, this study uses the results of questionnaires from respondents, as well as interviews with shareholders as data that is analyzed descriptively qualitatively. The research sample is S3-PVKT students and entrepreneurship lecturers. The research results are as follows: (1) S3-PVKT entrepreneurial learning competencies are supported by 21st century competencies, namely: (a) Critical thinking and problem solving; (b) Communication skills, (c) Collaboration, and (d) Creativity and Innovation; (2) Entrepreneurial competencies that can be used to support S3-PVKT entrepreneurship learning are: (a) Core characteristics of entrepreneurship, (b) Entrepreneurial philosophy, (c) Entrepreneurial business, (d) Academic entrepreneur, (e) Government Entrepreneur, (f) ) Social entrepreneur, and (g) Leadership; and (3) Entrepreneurship Course Competencies for the S3-PVKT study program are the result of integrating 21st century competencies with core entrepreneurial competencies. The outputs of this research are in the form of National Journals, National Proceedings and Intellectual Property Rights.Keywords: Integration, Learning, 21st Century Skills, Entrepreneurship